Comparison of infants and children with urolithiasis: A large case series - GÖKCE, İBRAHİM (My University, 2022)
We evaluated the demographic features, etiologic risk factors, treatment strategies, and outcome of the infants and children with urolithiasis (UL). A retrospective multicenter study was conducted including 23 Pediatric Nephrology centers in Turkey. The medical records of 2513 children with UL were reviewed. One thousand, three hundred and four boys and 1209 girls (1.1:1) were reported. The mean age at diagnosis was 39.5 +/- 35 months (0.4-231 months), and 1262 patients (50.2%) were in the first year of life (infants). Most of the cases with infantile UL were diagnosed incidentally. Microlithiasis (< 3 mm) was found in 794 patients (31.6%), and 64.5% of the patients with microlithiasis were infants. Stones were located in the pelvis-calyces in 63.2% (n: 1530) of the cases. The most common stone type was calcium oxalate (64.6%). Hypocitraturia was the most common metabolic risk factor (MRF) in children older than 12 months, but in infancy, hypercalciuria was more common. Fifty-five percent of the patients had received at least one medical treatment, mostly potassium citrate. At the end of a year\"s follow-up, most of the patients with microlithiasis (85%) showed spontaneous remission. The rate of spontaneous stone resolution in infants was higher than in children. Spontaneous remission rate was higher in cases with MRF ( - ) stones than in MRF ( +) stones. However, remission rate with medical treatment was higher in cases with MRF ( +) stones. This study represents the results of a large series of infants and children with UL and showed that there are several differences such as underlying metabolic and anatomic abnormalities, clinical course, and stone remission rates between infants and children with urinary stone disease.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Nephrology; ÜROLOJİ VE NEFROLOJİ; Klinik Tıp; Klinik Tıp (MED); UROLOGY & NEPHROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Üroloji; Urology; Urolithiasis; Infants; Children; Risk factors; Outcome; METABOLIC RISK-FACTORS; URINARY STONE DISEASE; PEDIATRIC UROLITHIASIS; VITAMIN-D; 1ST YEAR; EPIDEMIOLOGY; EXPERIENCE; DIAGNOSIS; AGE; Urolithiasis; Infants; Children; Risk factors; Outcome